2013
DOI: 10.1002/ejoc.201301006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Azulene‐Substituted Donor–Acceptor Chromophores Connected by Arylamine Cores

Abstract: 1‐Ethynylazulenes connected by several arylamine cores reacted with tetracyanoethylene (TCNE) and 7,7,8,8‐tetracyanoquinodimethane (TCNQ) in a formal [2+2] cycloaddition–cycloreversion reaction to afford the corresponding tetracyanobutadiene (TCBD) and dicyanoquinodimethane (DCNQ) chromophores, respectively, in excellent yields. The intramolecular charge‐transfer (ICT) characters between the donor (azulene and arylamine cores) and acceptor (TCBD and DCNQ units) moieties were investigated by UV/Vis spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…[19] Recently, we have developed various redoxactive chromophores for the creation of stabilized electro-7 chromic materials. [20] As a part of the study, we have reported several TCBD derivatives bearing azulenyl, [10][11][12]14] ferrocenyl, [21] and 2-oxo-2H-cyclohepta[b]-3-furyl [22] substituents, and we have identified some hybrid structures of violene and cyanine with redox activities. [23] Similarly to the TCBD derivatives described previously, these new 1-AzTCBD compounds connected through a 1,3,5-tri(1-azulenyl)benzene core should exhibit a reversible color change under electrochemical reaction conditions, because these compounds showed highly reversible redox waves by CV.…”
Section: Electrochemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…[19] Recently, we have developed various redoxactive chromophores for the creation of stabilized electro-7 chromic materials. [20] As a part of the study, we have reported several TCBD derivatives bearing azulenyl, [10][11][12]14] ferrocenyl, [21] and 2-oxo-2H-cyclohepta[b]-3-furyl [22] substituents, and we have identified some hybrid structures of violene and cyanine with redox activities. [23] Similarly to the TCBD derivatives described previously, these new 1-AzTCBD compounds connected through a 1,3,5-tri(1-azulenyl)benzene core should exhibit a reversible color change under electrochemical reaction conditions, because these compounds showed highly reversible redox waves by CV.…”
Section: Electrochemistrymentioning
confidence: 99%
“…Recently, we reported the redox potentials of a series of TCBD derivatives. [10][11][12]14] The study revealed that the first reduction potentials of the 1-AzTCBD compounds substituted by π-electron cores decreased as the number of substituted TCBD units increased. With respect to the number of stages for the reduction, Diederich et al reported that the compound with three DAA-substituted TCBD units connected by a 1,3,5-benzenetriyl spacer shows a six-stage reversible reduction wave within a narrow potential range.…”
Section: Electrochemistrymentioning
confidence: 99%
See 3 more Smart Citations